Moral development, affectivity and complexity: depletion of rationalist moral theories as of Carol Gilligan - da Silvaa, Matheus Estevão Ferreira [UNESP] (FapUNIFESP (SciELO), 2024)
The moral theories of Jean Piaget and Lawrence Kohlberg are accused of depletion. This depletion would be mainly due to its limitations in contemplating the complexity involved in moral development, such as the role of affectivity in this process. Based on the pioneering work of Carol Gilligan that stuck to this relationship between cognition and affectivity, several theories emerged with their own propositions aimed at remedying the limitations of their predecessors, which could therefore be said to be post-Kohlberguian. This article aims to discuss the issue of complexity in moral development, especially regarding the influence of affectivity in this process, initially unveiled from Gilligan. It is concluded that if there is, in fact, such depletion, the post-Kohlberguian theories that consider complexity, indebted to Gilligan’s pioneering work that served as a reference, seem to have renewed the field of investigation for another cycle of decades of study on moral development.
Desarrollo moral, afectividad y complejidad: agotamiento de las teorías morales racionalistas desde Carol Gilligan
Développement moral, affectivité et complexité: l’épuisement des théories morales rationalistes à partir de Carol Gilligan
Keywords: afectividad; afetividade; affectivity; affectivité; Carol Gilligan; complejidad; complexidade; complexity; complexité; desarrollo moral; desenvolvimento moral; développement moral; moral development; racionalismo; rationalism; rationalisme